The experimental manipulation of atmospheric drought: Teasing out the role of microclimate in biodiversity experiments. (21st February 2021) - Aguirre, Beatriz A.; Hsieh, Brian; Watson, Samantha J.; Wright, Alexandra J.
Abstract: Drought occurrence is increasing due to anthropogenic climate change. Drought can negatively affect plants via reduced water below‐ground and increased evaporative demand or vapour pressure deficit (VPD) above‐ground. Past work has shown that plant diversity can ameliorate the negative effects of drought in plant communities, but these results are inconsistent between experimental and natural drought studies. Furthermore, while studies on the negative effects of reduced soil moisture on plant growth in drought experiments are abundant, the effects of predicted increases in atmospheric VPD have been neglected. We directly manipulated atmospheric relative humidity in a biodiversity and drought experiment at the California State University, Los Angeles (CA, USA) under three atmospheric conditions (ambient, dehumidified and humidified), two treatments of native perennial grass diversity (monoculture and eight species polyculture) and two soil drought treatments (control and drought). We assessed both polyculture plant community and individual species ( Poa secunda ) responses to atmospheric drought and soil drought. We found that soil drought only limits above‐ground biomass production when atmospheric conditions are also dry. We also found that P. secunda was limited by increased competition in polyculture when ambient atmospheric conditions were humid but was facilitated by diversity when atmospheric conditions were dry. Synthesis . Higher diversity ecosystems may be capable of protecting individual species from the negative effects of drought (facilitation). Without careful experimental manipulation of atmospheric drought, this important mechanism will be missed. Abstract : We found that whole community biomass is reduced by soil drought only when atmospheric conditions are also dry. We demonstrate that competitive interactions may be more prominent in higher diversity communities when relative humidity is high. However, when relative humidity is low, facilitative interactions may dominate. Globally distributed drought experiments may need to be reconsidered. Resumen: La sequía está aumentando debido al cambio climático antropogénico. La sequía puede afectar negativamente a las plantas a través de la reducción del agua subterránea y el aumento de la demanda evaporativa o el déficit de la presión de vapor del aire (DPV) en la superficie atmosférica. Estudios anteriores han demostrado que la diversidad de plantas puede mejorar los efectos negativos de la sequía en las comunidades con plantas, pero estos resultados son inconsistentes entre los estudios experimentales y de sequía natural. Además, aunque abundan los estudios sobre los efectos negativos de la reducción del agua subterránea en el crecimiento de las plantas en los experimentos de sequía, se han descuidado los efectos de los aumentos previstos en la DPV atmosférica. Manipulamos directamente la humedad relativa atmosférica en un experimento de biodiversidad y sequía en la Universidad Estatal de California, Los Ángeles (CA, EE. UU.) bajo tres condiciones atmosféricas (ambiente, deshumidificado y humidificado), dos tratamientos de gramíneas perennes nativas diversas (monocultivo y ocho especies de policultivo), y dos tratamientos de sequía subterránea (control y sequía). Evaluamos a la comunidad de plantas de policultivo y a especies individuales ( Poa secunda ) de acorde a la reacción de la sequía atmosférica y la sequía subterránea. Encontramos que la sequía subterránea solo limita la producción de biomasa aérea cuando las condiciones atmosféricas también estàn secas. También encontramos que la P. secunda estaba limitada por una mayor competencia en el policultivo cuando las condiciones atmosféricas ambientales eran húmedas, pero se vio facilitada por la diversidad cuando las condiciones atmosféricas estaban secas. Síntesis . Los ecosistemas de mayor diversidad pueden ser capaces de proteger especies individuales de los efectos negativos de la sequía (facilitación). Sin una cuidadosa manipulación experimental de la sequía atmosférica, este importante mecanismo se perderá.